COMPARISON OF PERIOPERATIVE FACTORS BETWEEN LAPAROSCOPIC AND OPEN NEPHRECTOMY (The Research of Medical Science Review, 2025)
Objectives: To compare between operating time, blood loss, post operative pain score, wound infection, hospital stay and return to normal daily life activities in patients undergoing laparoscopic vs open nephrectomies Study Design: Quasi Experimental Interventional Study Design Place and Duration of Study: Armed Forces Institute of Urology, Rawalpindi from June 2024-February 2025 Methodology: A total of 206 patients with benign and malignant renal diseases were selected through convenience sampling and randomly divided into two groups. Cases of Group-A (laparoscopic nephrectomy) whereas cases in Group-B (open nephrectomy). Intra operative time, intra operative blood loss, post operative pain score using VAS after 48 hours of surgery, post operative wound infection on day 7, hospital stay and return to normal daily life activities were compared between the two study groups. Results: Time of surgery in Group-A was less compared to Group-B (open nephrectomy) with a statistical significance of p=0.003. Blood loss had a statistical significance of p=0.00 in Group-A (laparoscopic nephrectomy) compared to Group-B (open nephrectomy). Post operative pain was better tolerated in Group-A (laparoscopic nephrectomy) (p=0.00) at 48 hours after surgery, wound infection on day 7 was less in Group-A (laparoscopic nephrectomy) (p=0.00), hospital stay was less and patients were discharged earlier compared to Group-B (open nephrectomy) (p=0.00). Conclusion: Group A Laparoscopic nephrectomy provides superior outcomes compared to traditional Group B open nephrectomy in terms of peri operative factors.